Meat quality characteristics of three South African game species : black wildebeest (Connochaetes gnou), blue wildebeest (Connochaetes taurinus) and mountain reedbuck (Redunca fulvorufula) - Van Schalkwyk, Sunet (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Consumer Science)--Stellenbosch University, 2004.